COMPARATIVE EFFICIENCY AND TOLERABILITY OF CURRENT THERAPIES FOR EARLY RHEUMATOID ARTHRITIS - E. V. Fedorenko; G. V. Lukina; Ya. A. Sigidin; E. L. Luchikhina; D. E. Karateev (Научно-практическая ревматология)
Objective: to compare the efficiency and safety of four treatment regimens using methotrexate (MT),  leflunomide (LEF),  and a combination  of MT and glucocorticoids  (GC)  for early rheumatoid  arthritis (RA) (disease duration <2 years).Subjects and methods. 141 patients with early RA (of them there were 122 women; mean age 51 years; mean disease duration  7.8 months;  mean DAS28 6.0) were randomized  to 4 treatment groups: 1) MT 10–20 mg/week (n = 35); 2) MT 10–20 mg/week + oral GC equivalent to 10 mg/day of prednisolone  (n = 34); 3) MT 10–20 mg/week + oral CG + single intravenous administration of methylprednisolone (MP) 1000 mg at baseline (n = 35); 4) LEF 20 mg/day (n = 37). The patients were matched for main clinical and demographic  characteristics. The duration of treatment was 1 year. Its efficiency was evaluated according to the European  League Against Rheumatism (EULAR)  criteria.Results. 125 patients completed one-year treatment. At this time, 11.4% of the patients achieved remission (DAS28 <2.6) in the MT group, 37.5% in the MT+GC group, 29.4% in the MT+GC+MP group, and 16.2% in the LEF group. Adverse events, mainly of mild intensity, were recorded in 9 patients in each MT group. A total of 7 patients had to discontinue treatment because of its inefficiency.Conclusion. All the four therapy regimens demonstrated a significant efficiency in patients with early RA; the total remission rate was 24%. The combination  of MT and GC produced the most pronounced effect. The tolerability of treatment was good in all groups.